Chinese herbal medicine for the treatment of chronic fatigue syndrome: A systematic review and meta-analysis - Zhang, Yang; Jin, Fangfang; Wei, Xing; Jin, Qiuyu; Xie, Jingri; Pan, Yujia; Shen, Wenjuan (Frontiers in Pharmacology, 2022)
Objectives:.This meta-analysis aimed to assess the effectiveness and safety of Chinese herbal medicine (CHM) in treating chronic fatigue syndrome (CFS). Methods: Nine electronic databases were searched from inception to May 2022. Two reviewers screened studies, extracted the data and assessed risk of bias independently. The meta-analysis was performed using the Stata 12.0 software. Results: Eighty-five RCTs which explored the efficacy of 69 kinds of Chinese herbal formulas with various dosage forms (decoction, granule, oral liquid, pill, ointment, capsule, and herbal porridge), involving 7044 participants were identified. This meta-analysis showed that application of CHM for CFS can decrease Fatigue Scale (FS-14) score (WMD: –1.77; 95%CI: –1.96 to –1.57; P < 0.01), Fatigue Assessment Instrument (FAI) score (WMD: –15.75; 95%CI: –26.89 to –4.61; P < 0.01), Self-Rating Scale of mental state (SCL-90) score (WMD: –9.72; 95% CI:–12.26 to –7.18; p < 0.001), Self-Rating Anxiety Scale (SAS) score (WMD: –7.07; 95% CI: –9.96 to –4.19; P < 0.01), Self-Rating Depression Scale (SDS) score (WMD: –5.45; 95% CI: –6.82 to –4.08; P < 0.01), and clinical symptom score (WMD: –5.41; 95%CI: –6.16 to –4.65; P < 0.001) and improve IGA (WMD: 0.30; 95%CI: 0.20 to 0.41; P < 0.01), IGG (WMD: 1.74; 95%CI: 0.87 to 2.62; P < 0.01), IGM (WMD: 0.21; 95%CI: 0.14 to 0.29; P < 0.01) as well as the effective rate (RR = 1.42; 95%CI: 1.34 to 1.50; P < 0.01). While natural killer (NK) cell levels did not change significantly. The included studies did not report any serious adverse events. In addition, the methodology quality of the included RCTs was generally not high. Conclusion: Our study showed that CHM seems to be effective and safe in the treatment of CFS. However, given the poor quality of reports from these studies, the results should be interpreted cautiously, and more international multi-centered, double-blinded, well-designed, randomized controlled trials are needed in future research.